PENGARUH GRID RATI TERHADAP TINGKAT KEHITAMAN FILM DENGAN MENGGUNAKAN SINAR-X - Herlina, Yetti; Ratnawati, I Gusti Agung Ayu; Sudarsana, I Wayan Balik (BULETIN FISIKA, 2015)
Radiography quality is radiography ability to provide clear information about the object being examined. One of the important things that punch in a radiography with respect to the quality of the radiography contrast. Radiography contrast is obtained by measuring the density with a densitometer. A good radiography can be viewed from various aspect, one of which is contrast, lack of radiation scattering that occurs is essential to obtain optimal contras, it can be obtained in several ways such as irradiation (collimation to taste) and the used of technict kV. Movie density level depends on the density of the material transmitted by, the density on the movie influenced in grid ratio. Density increases with increasing grid ratio. The larger the grid ratio used the greater the darknes of the movies. Measurement with uji t statistic paired where the hypothesis if the P value (sig) ‹ ? (5%) then H 0 is the rejected and if the P value (sig) › ? (5%) then H 0 is accepted and if the value t hitung › t tabel then H 0 is rejected and if the t hitung ‹ t tabel then H 0 is accepted so it can be inferrent grid ratio of the obtained significant results, so the larger the grid ratio comparison is used then the grid the greater the darkness of the movie.